2006
DOI: 10.1103/physrevlett.96.036406
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Ferromagnetism from Statistical Transmutation in Two Dimensions

Abstract: The total spin of the ground state is calculated in the U-->infinity Hubbard model with uniform magnetic flux perpendicular to a square lattice, in the absence of Zeeman coupling. It is found that the saturated ferromagnetism emerges in a rather wide region in the space of the flux density phi and the electron density ne. In particular, the saturated ferromagnetism at phi=ne is induced by the formation of a spin-1/2 boson, which is a composite of an electron and the unit flux quantum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…1 of Ref. [2].) It is found that the saturated ferromagnetism (i.e., S tot ¼ S max ¼ N e =2) emerges in a rather wide region in the ðn e ; fÞ space.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1 of Ref. [2].) It is found that the saturated ferromagnetism (i.e., S tot ¼ S max ¼ N e =2) emerges in a rather wide region in the ðn e ; fÞ space.…”
Section: Resultsmentioning
confidence: 95%
“…We first calculate the total spin S tot of the ground state as functions of the electron density (n e ¼ N e =N) and the flux per plaquette (f) in the model (2), where N e is the number of electrons. (See Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, and the corresponding periodical boundary conditions are adopted. It should be noted that translational and macroscopic time-reversal symmetries make our model distinct from the uniform flux case, where the energy spectrum exhibits the fractal Hofstadter butterfly and the uniform flux induces a saturated FM from statistical transmutation at a flux quantum per electron [8].…”
Section: Gs Energymentioning
confidence: 97%
“…(For a related discussion for spinful electrons, see Ref. [17].) Numerical results for the square lattices of various sizes up to 26 sites (not shown) suggest that the energy difference is nonvanishing in the thermodynamic limit.…”
mentioning
confidence: 99%